2020
DOI: 10.1073/pnas.1913334117
|View full text |Cite
|
Sign up to set email alerts
|

Lck bound to coreceptor is less active than free Lck

Abstract: Src family kinase Lck plays critical roles during T cell development and activation, as it phosphorylates the TCR/CD3 complex to initiate TCR signaling. Lck is present either in coreceptor-bound or coreceptor-unbound (free) forms, and we here present evidence that the two pools of Lck have different molecular properties. We discovered that the free Lck fraction exhibited higher mobility than CD8α-bound Lck in OT-I T hybridoma cells. The free Lck pool showed more activating Y394 phosphorylation than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Moreover, high expression of CD3E and CD3D gene were reported significantly related to positive OS in CESC ( Wang et al, 2019b ). LCK, also known as lymphocyte-specific protein tyrosine kinase p56, was found as a key molecule in T cell activation by phosphorylating the TCR/CD3 complex to initiate TCR signaling ( Wei et al, 2020 ). Recent studies showed that the improved LCK activity was contributed to improve the efficacy of chimeric antigen receptors (CARs) immunotherapy in cancers ( Gulati et al, 2018 ; Bommhardt et al, 2019 ; Suryadevara et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high expression of CD3E and CD3D gene were reported significantly related to positive OS in CESC ( Wang et al, 2019b ). LCK, also known as lymphocyte-specific protein tyrosine kinase p56, was found as a key molecule in T cell activation by phosphorylating the TCR/CD3 complex to initiate TCR signaling ( Wei et al, 2020 ). Recent studies showed that the improved LCK activity was contributed to improve the efficacy of chimeric antigen receptors (CARs) immunotherapy in cancers ( Gulati et al, 2018 ; Bommhardt et al, 2019 ; Suryadevara et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…And other genes are thought to be closely related to pancreatic cancer, such as LCK 34 . LCK is critical for T cell development and activation, as it is the first kinase to divert TCR signalling 35 . What's more, LCK, CD247, CD27, CD3D, and CD74 were mentioned as upregulated genes in anti-PDL1 treated mice and downregulated genes in inflammatory breast cancer with PDL1 overexpression 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…CD4 dwell time on pMHCII is proportional, yet faster, to TCR dwell time, suggesting that TCR:pMHCII interaction kinetics would directly affect the duration that CD4 molecules cycle through the immunological synapse in a processive-like manner ( 88 ). Additionally, compared to coreceptor-bound Lck, CD4-free Lck is phosphorylated more at its Y394 activation site, with higher kinase activity and mobility ( 81 ); thus, it may be that if CD4-free Lck is prevented from interacting with the immunological synapse, activation may be reduced. TCR-pMHCII interactions are highly ordered and uniform, increasing the likelihood that the spatial relationship between Lck and the ITAMs of the TCR-SCS or flTCRs are consistent.…”
Section: Discussionmentioning
confidence: 99%